Development of Tpsr Learning Devices Based Activity Materials on Social Skills Athletic - Al Fitri Nurani; Febrita Paulina Heynoek; Rama Kurniawan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
The aim is to develop learning tools based on social skills using the Teaching Personal And Social Responsibility (TPSR) learning model. Research and development use a procedural model,  The development steps refer to Research and Development (R&D) with 10th steps. Research and development use the 7th research step under the conditions and situations. Data collection uses a questionnaire/questionnaire instrument. The trial subjects of this study were (a) individual subjects belong expert validators and (b) prospective users consisting of 5 physical education teachers (PE) and a total of 10 students for SMA/SMK small groups testing and 14 teachers and 60 students for substantial group testing. The data analysis technique used descriptive quantitative, qualitative. The results of the data analysis showed a small group test of teachers with a feasibility level of 82% and students of 74.9%. Meanwhile, for the substantial group test, the feasibility level of teachers is 87%, students are 80.2%. The conclusion is worth applying and using.